연속식 다중 초음파 반응조에서 TCE의 초음파 분해 - 이민주(Min Ju Lee); 오재일(Jei Il Oh) (Daehan hwan'gyeong gonghag hoeji, 2009)
To test applicability for continuous flow treatment of ultrasound technology, sonolysis of TCE aqueous solution using 584 kHz multi irradiation reactor was performed under batch and continuous flow conditions. Under batch condition (3 and 4 sides irradiation, 600 W), first order degradation rate constant of TCE was higher under 4 sides than 3 sides irradiation conditions, while the generation of $H_2O_2$ and chloride was similar under both irradiation conditions. Under continuous flow condition with 4 sides irradiation, removal efficiencies of TCE in steady-state were decreased from 83 to 48% with increasing flow rate from 67 to 300 mL/min at 600 W, and were increased from 14 to 75% with increasing acoustic power from 100 to 600 W at 100 mL/min. Removal efficiency of TCE in groundwater was decreased 10% compared to in distilled water at 100 mL/min and 600 W. 초음파 기술의 연속식 처리 적용성에 대한 연구를 수행하기 위해서 584 kHz 다중 조사 반응조를 제작하여 회분식과 연속식 조건에서 TCE 수용액의 초음파 분해 실험을 수행하였다. 600 W의 3면과 4면 조사 조건에서의 회분식 실험 결과, TCE의 1차 저감 속도 상수는 4면 조사 조건에서 더욱 큰 것으로 나타났으며, $H_2O_2$와 CT의 발생은 두 조건 모두 비슷한 것으로 나타났다. 600 W 4면 다중 조사 조건에서 67${\sim}$300 mL/min의 유량 범위에서 정상 상태에서의 TCE 제거율은 83에서 48%로 약 35% 감소하였다. 100 mL/min, 600 W의 4면 다중 초음파 조사 조건에서 100${\sim}$600 W로 초음파 출력을 증가시킬 때 정상 상태에서 TCE의 제거율은 14에서 75%로 61% 증가하였다. 600 W의 4면 다중 조사 조건에서 100mL/min의 유량으로 실제 TCE 오염지하수에 대한 초음파 분해를 수행한 결과 증류수에서의 제거율 75%에 비해 약 10% 정도 감소하여 약 65%로 나타났다.